The problem of pain - Lewis, C. S. (Clive Staples), 1898-1963.; Whitfield, Robert; Blackstone Audiobooks; NetLibrary, Inc. ([Ashland, Or.] : Blackstone Audiobooks ; [Boulder, Colo. : Made available electronically by] NetLibrary, 2007)
For centuries, Christians have been tormented by one question above all: "If God is good and all powerful, why does he allow his creatures to suffer pain?" C.S. Lewis sets out to disentangle this knotty issue and offer an answer.
System requirements: Windows Media Player compatible, check NetLibrary website for version information; iPod or iPhone or mp3 compatible device.
Mode of access: World Wide Web.
Unabridged.
Audio file.
Title from image on Web page (viewed January 17, 2007).
Previously released on compact disc, 2000.
Keywords: Pain -- Religious aspects -- Christianity; Suffering -- Religious aspects -- Christianity; Good and evil; Providence and government of God; Audiobooks; Downloadable audio books